An economic analysis of biogas-biomethane chain from animal residues in Italy. (1st September 2019) - Cucchiella, Federica; D'Adamo, Idiano; Gastaldi, Massimo
Abstract: The green revolution represents a substantial investment plan on renewable energy resources (RESs) reducing the country's dependence on fossil fuels energy. Currently, some resources are not completely exploited and the transformation of waste residues into green energy is able to develop circular economy models. Europe has a great potential coming from animal residues and the transport sector has a weak growth of RESs. Biomethane, also called green gas, is a possible valid solution. This work provides an economic analysis regarding both biogas and biomethane plants that use several typologies of animal residues. Net Present Value (NPV) and Discounted Payback Time (DPBT) are used as indexes. The production of electricity by biogas plants contributes to reducing the levels of emissions, but its upgrading can conduct to increase environmental performance. This is not coupled with an increase in profits. Results of the work define the minimum size in which both biogas and biomethane plants are profitable and the key-role of subsidies trying to provide policy guidance to governments and planners. Graphical abstract: Image 1052937 Highlights: Animal residues are a resource and not an issue. 200 kW is the minimum biogas size in which the profitability is verified. 350 m 3 /h is the minimum biomethane size in which the profitability is reached. Biomethane plant is less profitable than biogas one. Economic results are mainly determined by the subsidies.